Ação da rutina em um modelo de exposição aos metais cobre e zinco em Caenorhabditis elegans com superprodução de huntingtina - Cordeiro, Larissa Marafiga (2023)
Huntington's disease (HD) is a progressive, hereditary neurodegenerative disease caused due to a mutation in the huntingtin gene that contains an abnormal expansion of cytosine-adenineguanine (CAG) repeats, leading to a polyglutamine (polyQ) chain of variable length. The mutation confers toxic functions on the mutant huntingtin protein, causing neurodegeneration. HD pathology results in loss of neuronal cells, motor changes, dementia and is currently a disease with no cure. It is known that metal accumulation is found in the pathologically affected regions of many neurodegenerative diseases. The essential metals Copper and Zinc are necessary in small concentrations for metabolic functions, but can, however, produce toxic effects in high concentrations. Furthermore, there is great concern regarding environmental pollution by metals, as urban environments are places subject to significant levels of contamination and, consequently, are the areas with the greatest exposure of metals to the population, whether through inhalation of dust or ingestion of contaminated soil through food. Rutin is a flavonoid found in several plants, such as buckwheat, some teas and fruits, making it easily accessible and low cost to the entire population. Therefore, this work investigated the effect of rutin on neurotoxic effects caused by Copper and Zinc in a HD model in Caenorhabditis elegans. The evaluation of the mixture of metals in chronic form and concentrations permitted by Brazilian legislation regarding residential soils was investigated for the first time. In general, exposure to metals and their mixture led to locomotor and body changes, in addition to a delay in the development of the worms, and affected behaviors related to ASH neurons and touch receptor neurons. Furthermore, it caused an increase in muscle and neuronal protein aggregates, leading to neurodegeneration. The neuroprotective effect of rutin was verified, the flavonoid was able to reduce protein aggregates and neurodegeneration. It has been proposed that rutin acts through mechanisms involving antioxidant properties, through increased expression of antioxidant enzymes and chaperones, in addition to acting against metals. Taken together, our data provide new insights into the guiding values of soil quality, analyzed chronically and in mixed metals, as well as new strategies for future treatments of neurodegenerative diseases caused by the aggregation of metal-related proteins.